1998
DOI: 10.2527/1998.7692331x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic markers on selection.

Abstract: Genetic marker technologies, such as marker-assisted selection, parentage identification, and gene introgression can be applied to livestock selection programs. Highly saturated genetic maps are now available for cattle, swine, and sheep to provide the genetic framework for developing MAS programs. These programs rely on three phases for commercialization of the technology: the detection phase, in which quantitative trait loci are located and their effects on the phenotype measured; the evaluation phase, in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 35 publications
0
48
0
2
Order By: Relevance
“…Efficiency of MAS was also related to the degree of difficulty of measuring the trait, with efficiency increasing for more difficult-to-measure traits such as carcass and meat quality attributes, efficiency of feed utilisation and resistance to diseases and parasites that affect production or quality attributes. As heritability increases, the increase in response owing to the incorporation of marker information is reduced relative to selection on breeding value estimated from phenotypic data alone (Davis and DeNise 1998). Gibson (1994) and Garrick (1997) used simulation to predict response to selection in a population in which a QTL and linked markers were segregating.…”
Section: Use Of Marker-assisted Selection In Breeding Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficiency of MAS was also related to the degree of difficulty of measuring the trait, with efficiency increasing for more difficult-to-measure traits such as carcass and meat quality attributes, efficiency of feed utilisation and resistance to diseases and parasites that affect production or quality attributes. As heritability increases, the increase in response owing to the incorporation of marker information is reduced relative to selection on breeding value estimated from phenotypic data alone (Davis and DeNise 1998). Gibson (1994) and Garrick (1997) used simulation to predict response to selection in a population in which a QTL and linked markers were segregating.…”
Section: Use Of Marker-assisted Selection In Breeding Programsmentioning
confidence: 99%
“…A number of simulation studies have compared traditional selection programs to those incorporating some combination of marker and phenotypic information. Davis and DeNise (1998) summarised the factors that influence the rate of genetic change in these simulated studies, as shown in Table 13. Strategies using both marker and phenotypic information were always superior to phenotypic selection alone in early generations.…”
Section: Use Of Marker-assisted Selection In Breeding Programsmentioning
confidence: 99%
“…Genetic markers can be used to identify specific regions of chromosomes where genes affecting quantitative traits are located, i.e., QTL (Davis and DeNise, 1998). These techniques can directly confirm the potential parent-to-offspring transfer of those genes associated with a desired trait (Akhimienmhonan and Vercammen, 2007).…”
Section: Genetic Markersmentioning
confidence: 99%
“…MacNeil and Grosz (2002) have stated that the identification of QTL has the potential to significantly increase the genetic improvement rate through the implementation of marker-assisted selection (MAS). For traits difficult or expensive to determine, with low heritability, late expression or measured only after slaughter, MAS can substantially increase the rate of response compared to selection based exclusively on estimates of performance values (Davis and DeNise, 1998). The use of MAS also allows the opportunity for more efficient breakage of antagonistic genetic correlations between characters (Grosz and MacNeil, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait loci have been detected in experimental and commercial bovine, swine and ovine populations (Davis and DeNise, 1998). There are several described bovine QTL affecting many characteristics.…”
Section: Introductionmentioning
confidence: 99%